2004
DOI: 10.1007/s00125-004-1486-4
|View full text |Cite
|
Sign up to set email alerts
|

Albumin excretion in diabetic patients in the setting of acute myocardial infarction: association with 3-year mortality

Abstract: Aims/hypothesis. Diabetes mellitus is associated with increased mortality in subjects with acute myocardial infarction (AMI). We aimed to estimate the risk of mortality in AMI patients with and without diabetes using the urinary albumin : creatinine ratio (ACR).Methods. This is a prospective study of 121 consecutive, non-selected diabetic AMI patients, 121 age-and sex-matched non-diabetic AMI patients and 61 diabetic non-AMI outpatients as control subjects. All data were obtained during the first 7 days of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In addition, albuminuria has been reported to be an independent risk factor for cardiovascular morbidity and mortality (12)(13)(14). The present study showed that a reduction of microalbuminuria is associated with a lower risk for cardiovascular and renal events.…”
supporting
confidence: 63%
“…In addition, albuminuria has been reported to be an independent risk factor for cardiovascular morbidity and mortality (12)(13)(14). The present study showed that a reduction of microalbuminuria is associated with a lower risk for cardiovascular and renal events.…”
supporting
confidence: 63%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] It is also associated with increased risk of death in patients with myocardial infarction. 16,17 Essential hypertension and microalbuminuria in nondiabetic individuals was first associated in 1974 18 and later confirmed in subsequent studies. 1,10,19 -21 Measurement of microalbuminuria is in some guidelines recommended for risk stratification in people with hypertension.…”
mentioning
confidence: 66%
“…Numerous studies in diabetic individuals with microalbuminuria demonstrate higher morbidity and mortality from cardiovascular disease (2-6). Microalbuminuria in diabetic subjects strongly predicts cardiovascular mortality even in the setting of acute myocardial infarction (24). This evidence suggests that remission/regression of microalbuminuria results in reduction of risk from cardiovascular disease.…”
Section: Discussionmentioning
confidence: 90%